Melestarikan Lingkungan Hidup Secara Komprehensif - Paulus Erwin Sasmito (Jurnal Orientasi Baru, 2015)
The focus of this paper is how to preserve the living environment comprehensively in crisis situation in which a very poor environment. The method used for writing this article is a pastoral reflection method. The reflection comes from the real life or the experiences of environment crisis. The next step is to find out the crisis of fundamental method. The last stage of the pastoral reflection is presenting proposals for overcoming the crisis environment and with a comprehensive approach to seeking ways to conserve the environment concrete. The conclusion from this reflection is the environmental crisis occurred because of the consciousness, Humans mentality and responsibility are integral part of nature that must preserve the unity of his life in his environment which sometimes obscured by the mentality of anthropocentric (means human as the center and the ruler of the universe) and biocentrism (humans consciousness as a part of the living thing). To preserve nature, human beings need to build awareness and ecological mentality, that is, every person is aware and living life in a synergistic networking with others, Gods creations and God. Preserving environment is a human responsibility to cherish and develop comprehensive and integral life.